2012
DOI: 10.1016/j.compscitech.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fatigue behaviour of flax/epoxy and glass/epoxy composites

Abstract: International audienceExperimental investigations on flax and glass fabrics reinforced epoxy specimens, i.e. FFRE and GFRE, submitted to fatigue tests are presented in this paper. Samples having [0/90](3S) and [+/- 45](3S) stacking sequences, with similar fibre volume fractions have been tested under tension-tension fatigue loading. The specific stress-number of cycles to failure (S-N) curves, show that for the [0/90](3S) specimens, FFRE have lower fatigue endurance than GFRE, but the [+/- 45](3S) FFRE specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(125 citation statements)
references
References 18 publications
(31 reference statements)
10
104
0
2
Order By: Relevance
“…For low loading levels, the fatigue behavior of the composite is the same, which means a long term life (Liang et al 2012). The hybrid fatigue failure appears to be highly dependent on the loading level imposed (Silva et al 2009).…”
Section: Fig 6 S-n Curve Of Tension-compression Fatiguementioning
confidence: 92%
See 1 more Smart Citation
“…For low loading levels, the fatigue behavior of the composite is the same, which means a long term life (Liang et al 2012). The hybrid fatigue failure appears to be highly dependent on the loading level imposed (Silva et al 2009).…”
Section: Fig 6 S-n Curve Of Tension-compression Fatiguementioning
confidence: 92%
“…In composite materials, fatigue damage always reduces the stiffness as opposed to the strength of the composite (Liang et al 2012). The stiffness degradation (F/F0) is calculated by dividing the maximum load (F) for the imposed displacement level on the load that was obtained at the first cycle (F0), to estimate the progression of damage under cyclic loading.…”
Section: Fig 6 S-n Curve Of Tension-compression Fatiguementioning
confidence: 99%
“…The glass-based composites showed a steeper S-N diagram, which led to a more significant decrease in fatigue strength. In one study comparing the S-N curves of bidirectional flax and glass, glass had a steeper curve than flax composites (Liang et al 2012). bioresources.com Sharba et al (2016).…”
Section: Fig 4 Flexural Properties Of Compositesmentioning
confidence: 99%
“…UD glass fibre laminate with the highest fibre content loaded along fibre direction, exhibited the best fatigue resistance. In our previous study [17], the fatigue behaviours of flax/epoxy and glass/epoxy with the same stacking sequence and similar fibre volume fractions have been compared. It was shown that both materials have similar fatigue performance for low loading levels, i.e.…”
Section: Introductionmentioning
confidence: 99%